Investigating Problem Definition and End-User Involvement in Agile Projects that Use Lean Inceptions - Ferreira, Bruna; Kalinowski, Marcos; Gomes, Marcos Vinicius de Carvalho; Marques, Marcelo Cardoso; Lopes, Hélio; Barbosa, Simone D. J. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2021: Anais do XX Simpósio Brasileiro de Qualidade de Software, 2021)
Agile methods focus on high quality, frequent deliveries, and customer and development team communication. Despite emphasizing customer involvement, in practice end users commonly do not participate in the early stages of these methods; instead, other businessrelated customers represent them in defining end-user needs. As a result, the produced software often does not satisfy the actual users’ needs, and the User Experience (UX) suffers. User-centered design, Design Thinking, and Lean Startup have been combined with agile methods to support defining the problem focused on user needs and producing effective software. Lean Inception (LI) represents a workshop that combines Design Thinking and Lean Startup. However, the effectiveness of problem definition and enduser participation in LIs is little explored. This paper presents a case study addressing this gap, investigating the use of LIs to define the problem and how the participation of end users in this context contributes to the resulting UX. We conducted ten semistructured interviews with customers and end-users of an agile software project using LI. Our analysis suggests that, while LI supports the identification of business goals, more details about user needs and software requirements are needed to support designers and developers in understanding the problem and evaluating its feasibility. We also identified a mischaracterization of user journeys and personas in LIs due to the short time dedicated to their creation, hampering the discussion of relevant UX issues. Finally, we observed that, when end users were present in the early stages, they helped the development team to design software that fits into their routine, improving the UX and increasing its adoption. We qualitatively discuss these issues and gains of directly involving end users and not “proxy” stakeholders in LI’s.